Examining the social issues and challenges encountered by Bangladeshi foreign labors - Kharmeyni Jumbulingam; Hossam Fadel; H. M. Naseef Akbar Talukder; Ni Made Sumarningsih (Universitas Pendidikan Nasional, 2024)
This study focused on how the earnings of Bangladeshi foreign labor impacted the economic development of Bangladesh. The purpose of this research was to raise awareness of the problems faced by Bangladeshi laborers on short-term work visas in various foreign countries and to explore how society can address this significant social issue to eradicate the problems among the deprived poor people of the society. In this study, the researcher used a mixed approach of quantitative and qualitative methods. The main problem was the social challenges faced by Bangladeshi labor workers. This issue was important to address because it was necessary to advocate for the rights of the deprived people of Bangladesh. This study focused on the issues faced by Bangladeshi workers in foreign nations, such as Gulf countries and emerging Asian countries like Malaysia. Bangladeshi policymakers, economists, lawyers, and human rights activists found this study useful for their professions. This research employed a mixed method of qualitative and quantitative research.